2016
DOI: 10.1158/1078-0432.ccr-15-2547
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics Uncover the Biology behind the Responsiveness of Head and Neck Squamous Cell Cancer Patients to Cetuximab

Abstract: Purpose: To identify the tumor portrait of the minority of head and neck squamous cell carcinoma (HNSCC) patients with recurrent-metastatic (RM) disease who upon treatment with platinum-based chemotherapy plus cetuximab present a long-lasting response.Experimental Design: The gene expression of pretreatment samples from 40 HNSCC-RM patients, divided in two groups [14 long-progression-free survival (PFS) and 26 short-PFS (median ¼ 19 and 3 months, respectively)], was associated with PFS and was challenged again… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 35 publications
8
87
0
Order By: Relevance
“…Bossi et al . recently showed that patients with a long progression‐free survival under cetuximab maintenance therapy can be predominantly found in the basal subtype group . This is very much in line with our findings and supports the notion of prospective evaluation of gene expression profiles in regard to patient stratification.…”
Section: Discussionsupporting
confidence: 92%
“…Bossi et al . recently showed that patients with a long progression‐free survival under cetuximab maintenance therapy can be predominantly found in the basal subtype group . This is very much in line with our findings and supports the notion of prospective evaluation of gene expression profiles in regard to patient stratification.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 EGFR triggers multiple downstream signaling pathways linked to cell survival and proliferation, such as the STAT, SRC, PI3K and MAPK pathways [reviewed in Refs. [19][20][21][22] An additional common resistance mechanism to cetuximab is reactivation of signaling pathways due to upregulation and activation of alternative RTKs, which termed as a compensatory activation loop [reviewed in Ref. [3][4][5][12][13][14] Cetuximab inhibits tumor cell growth by preventing ligand binding to the extracellular domain of EGFR, thereby preventing the dimerization and auto-phosphorylation of this receptor and the subsequent activation of the signaling pathways downstream of EGFR.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Cancer Research, Bossi and colleagues (1) report that pretreatment tumor gene expression profiles (GEP) of recurrent/metastatic head and neck squamous cell carcinomas (HNSCC) from patients who experience prolonged response [median progression-free-survival (PFS) of 19 months] to treatment with palliative cetuximab-chemotherapy are characterized by basal subtype traits, and significantly differ from GEP of patients with short responses, thus highlighting the potential opportunity for the future development of a predictive gene signature to select HNSCC patients for cetuximab-chemotherapy. Cetuximab, a chimeric immunoglobulin G1 antibody to the Epidermal Growth Factor Receptor (EGFR) is the only "molecularly targeted" therapy in HNSCC.…”
mentioning
confidence: 99%